2017
DOI: 10.1248/bpb.b16-00917
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Surface of Silica Nanoparticles with Amino or Carboxyl Groups Decreases Their Cytotoxicity to Parenchymal Hepatocytes

Abstract: We previously reported that unmodified silica nanoparticles with diameters of 70 nm (nSP70) induced liver damage in mice, whereas nSP70 modified with carboxyl or amino groups did not. In addition, we have found that both unmodified and modified nSP70s localize in both Kupffer cells and parenchymal hepatocytes. We therefore evaluated the contributions of nSP70 uptake by these cell populations to liver damage. To this end, we pretreated mice with gadolinium (III) chloride hydrate (GdCl 3 ) to prevent nSP70 uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other findings have suggested that SiO 2 NP exposure is associated with respiratory and cardiovascular illnesses, multiple organ damage, oxidative stress, and cellular-and molecular-level damage (Chen et al, 2004;Chen and von Mikecz, 2005;Lin et al, 2006;Chen et al, 2008;Shang et al, 2009;Choi et al, 2010;Lu et al, 2010;Yang et al, 2010;van der Zande et al, 2014;Niu et al, 2016). Amine functionalized amorphous SiO 2 NPs have demonstrated less toxicity as compared to bare amorphous SiO 2 NPs in both previous in vitro and in vivo studies (Marzaioli et al, 2014;Nagano et al, 2017), although other studies have reported otherwise (Yu et al, 2011;Kurtz-Chalot et al, 2014). The varying toxicities of NH 2 -SiO 2 NPs may be attributed to the exposure conditions (Boussif et al, 1995;Xia et al, 2008;Hsiao et al, 2019) as well as the extent of amino group surface coverage (Yu et al, 2011;Morris et al, 2016) and steric hindrance brought about by the linker structure which binds the amino groups to the SiO 2 NP surface (Hsiao et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…Other findings have suggested that SiO 2 NP exposure is associated with respiratory and cardiovascular illnesses, multiple organ damage, oxidative stress, and cellular-and molecular-level damage (Chen et al, 2004;Chen and von Mikecz, 2005;Lin et al, 2006;Chen et al, 2008;Shang et al, 2009;Choi et al, 2010;Lu et al, 2010;Yang et al, 2010;van der Zande et al, 2014;Niu et al, 2016). Amine functionalized amorphous SiO 2 NPs have demonstrated less toxicity as compared to bare amorphous SiO 2 NPs in both previous in vitro and in vivo studies (Marzaioli et al, 2014;Nagano et al, 2017), although other studies have reported otherwise (Yu et al, 2011;Kurtz-Chalot et al, 2014). The varying toxicities of NH 2 -SiO 2 NPs may be attributed to the exposure conditions (Boussif et al, 1995;Xia et al, 2008;Hsiao et al, 2019) as well as the extent of amino group surface coverage (Yu et al, 2011;Morris et al, 2016) and steric hindrance brought about by the linker structure which binds the amino groups to the SiO 2 NP surface (Hsiao et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…In these processes, the surface of the NP is modified by functionalisation. Examples include the functionalisation of surface molecules (such as SNPs) with amino or carboxyl groups to decrease their cytotoxicity to parenchymal hepatocytes [ 153 ]. Grafting, in which functional moieties such as probe molecules and targeting ligands are covalently attached to NMs, has also been reported [ 154 , 155 ].…”
Section: Surface Nanoscale Topography As Effective Design Strategymentioning
confidence: 99%
“…This binding capability allows research to obtain the conjugation of amino acids, proteins, enzymes, antibodies, among others, increasing the functionality and specificity within the biomedical area. Additionally, it has been reported that amine functionalization over silica NPs decreases the toxicity levels compared with the non-functionalized silica NPs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This binding capability permits the conjugation of amino acids, proteins, enzymes, and antibodies, increasing the MNPs functionality and specificity. Additionally, it has been reported that amine functionalization over silica MNPs decreases their toxicity levels, compared with non-functionalized silica MNPs [26,27]. The coating and functionalization of MNPs with inorganic or organic layers is limited to 500 nm for their interaction with cell membranes and sizes below 100 nm can be accumulated by cellular endocytosis in tumors [28].…”
Section: Introductionmentioning
confidence: 99%